Integrating Socioeconomic and Ecological Perspectives: A Bibliometric Study on Sustainability and Resource Management - David, Rowena May T.; Maroma, Adrian P. (Future Science / FSH-PH Publications, 2025)
This study performs a detailed bibliometric analysis to trace the evolution of sustainability and livelihood research, mapping key ideas, interdisciplinary connections, and the thematic shift from purely economic models to integrated frameworks encompassing social and ecological resilience, adaptive governance, and institutional dynamics. Using a structured approach with Scopus data, co-citation and co-word analyses were performed via VOSviewer and Bibliometrix. This process, guided by strict criteria, generated citation networks and keyword co occurrence visualizations to map the field's intellectual and thematic structure. Findings confirm the enduring influence of foundational frameworks, notably the Sustainable Livelihoods Framework (SLF) and Ostrom's Institutional Analysis and Development (IAD) framework. Results indicate an accelerating trend toward interdisciplinary teamwork, sustainability education, entrepreneurship, and the role of digital technologies in enhancing livelihood resilience.These findings offer useful insights for policymakers, educators, and industry players. They highlight the need for adaptive governance, technological innovation, and community-led sustainability projects. Additionally, the study points out important research areas, including climate adaptation strategies, gender-inclusive sustainability policies, and digital changes in livelihood systems. By connecting theoretical and practical views, this study helps deepen our understanding of the changing landscape of sustainability and resource management. It suggests strategic directions for promoting global sustainable development.